Optimalisasi Dua Layanan Jaringan Internet Menggunakan Teknik Load Balancing dengan Metode Peer Connection Classifier (PCC) (Studi Kasus: Jaringan Internet Desa Banyuanyar Boyolali) - Hafizh, Afrianton Noor; Sulistyo, Wiwin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Load Balancing is a technique for distributing data traffic so that the workload is distributed evenly on 2 or more networks to maximize resource usage and improve performance. There are two ISPs for internet access services to the Banyuanyar Village Office, Boyolali, both of which have different bandwidths, namely from PT. Telkom has 100Mbps bandwidth and Kominfo has 50Mbps bandwidth. So here there will be dense network traffic if the internet network is not optimized.. In this case, it can be optimized using load balancing techniques on both ISPs by using the Peer Connection Classifier technique to group traffic and divide the load on both internet connection lines so as not to overload. So it can be concluded that by adding a proxy router device, configuring load balancing, and applying a hierarchical network-based network topology, it will optimize two internet network services at Banyuanyar Village Hall, Boyolali.
Keywords: Internet; Load Balancing; PCC